2004
DOI: 10.3748/wjg.v10.i12.1795
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of regurgitation and other symptoms of gastroesophageal reflux in Indonesian infants

Abstract: Regurgitation occurs frequently in Indonesian infants, and is a frequent cause of concern to mothers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
40
1
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 28 publications
3
40
1
3
Order By: Relevance
“…[2][3][4][5] However, published data to support this hypothesis are limited and few available data tend to suggest the contrary to common belief that infant…”
mentioning
confidence: 55%
See 3 more Smart Citations
“…[2][3][4][5] However, published data to support this hypothesis are limited and few available data tend to suggest the contrary to common belief that infant…”
mentioning
confidence: 55%
“…This agrees with the findings of other studies which show that regurgitation disappear almost completely at about the age of 1 year. [2][3][4][5] Regurgitation in infancy is the only symptomatic GER that is considered physiological as it believes to be benign and does not need any treatment or medical attention. 1,11 Summary of results from those studies is shown in Table 3.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was reported to be more common in Western countries than Eastern countries (5,6). In addition; recent studies in children have suggested that genetic factors may play a role in GERD, and thus it is claimed that its prevalence and severity might vary according to racial and ethnic background (7). The prevalence of GER (especially with regurgitation) in American infants was found to be 50% in 0 to 3-month-olds, 67% in those aged 4 to 6 months, 21% in 7 to 9-montholds and 5% in infants of 10 to 12 months; whereas it was found lower in Thai infants (2,5).…”
Section: Introductionmentioning
confidence: 99%